Face and Neck Pilomatricoma Excision Using an Endoscope‐Assisted Hairline Approach - Ken Woo; Dong Kun Lee; Seung Hoon Woo (OTO Open, 2025)
Abstract Objective Traditional transcutaneous approaches for pilomatricoma excision in the face and neck are effective but often leave conspicuous scars that compromise cosmetic outcomes. We aimed to evaluate a refined endoscope‐assisted hairline approach that uses a concealed scalp incision and enhanced endoscopic visualization to improve esthetic results while maintaining surgical efficacy. Study Design Prospective observational study. Setting Dankook University School of Medicine, Korea. Methods Fifty patients with benign pilomatricomas of the face and neck were prospectively enrolled and allocated into two groups. Group A (n = 25) underwent the refined endoscope‐assisted hairline approach, whereas Group B (n = 25) received the conventional transcutaneous approach. Clinical data including operative time and postoperative complications were recorded. Cosmetic outcomes were objectively evaluated using standardized photographic documentation and patient satisfaction scores collected at 3 and 12 months postoperatively. Results The mean operative time was significantly longer in Group A compared to Group B (P < .001), reflecting the technical intricacies of the hairline approach. No significant differences were observed between the two groups in hospital stay or overall complication rates. Importantly, cosmetic satisfaction scores were significantly higher in Group A (P < .001), with objective assessments consistently demonstrating reduced scar visibility and superior preservation of skin integrity. Conclusion The refined endoscope‐assisted hairline approach is a safe and highly effective technique for pilomatricoma excision in cosmetically sensitive facial and neck regions. This innovative method offers significant improvements in esthetic outcomes without compromising safety, representing a distinct advance over conventional methods.